Partially hydrolyzed formula with high sn-2 palmitic acid on eosinophils and outcomes in preterm infants: PRIOR secondary analysis - Zhuang, Jialu; Liu, Ye; Liu, Qiongyu; Wang, Jiaan; Liu, Songlin; Wu, Jing; Shen, Yanqing; Wang, Xuemin; Zhang, Hui; Yuan, Li; Chen, Jinwen; Geng, Ruizhen; et al. (Frontiers in Pharmacology, 2026)
BackgroundPreterm infants, with immature immune systems, are susceptible to type 2 inflammation, characterized by eosinophil recruitment, exacerbating intestinal and respiratory inflammation. Breastfeeding mitigates inflammation via sn-2 palmitic acid and immunomodulatory factors (e.g., IL-10), but formula feeding is often necessary due to clinical constraints. High sn-2 palmitic acid partially hydrolyzed formula (HPF) may reduce eosinophil-related inflammation by lowering protein immunogenicity, yet evidence is limited.MethodsThis secondary analysis of the ongoing PRIOR parallel-group randomized controlled trial (ChiCTR2400093296) (evaluating formula safety and growth-related outcomes) included 90 preterm infants (gestational age <34 weeks or birth weight <2000 g), randomized to HPF (n = 45) or standard preterm formula (SPF) (n = 45) using computer-generated randomization with allocation concealment. Infants were enrolled from 1 July 2024, to 30 June 2025, and followed weekly during hospitalization and monthly after discharge until a corrected age of 3 months. Primary outcomes were hematological parameters (including eosinophil counts) at discharge; secondary outcomes included hospital stay duration, necrotizing enterocolitis (NEC) incidence, and anemia management. Generalized additive models assessed eosinophil levels relative to corrected gestational age and formula exposure duration.ResultsEighty infants completed the in-hospital phase (HPF, n = 41; SPF, n = 39). Groups were similar in gestational age, birth weight, sex, and Apgar score (all p > 0.05). HPF showed a steeper decline trend in eosinophil percentage after prolonged exposure (>25 days, p = 0.053), suggesting inflammation suppression. Hospital stay duration (HPF, 30 (17–38) days vs. SPF, 27 (20–36) days; p = 0.825) and NEC incidence (2.4% vs. 2.4%; p = 1.000) did not differ significantly.ConclusionHPF demonstrates potential in reducing eosinophil-mediated inflammation in preterm infants but has no significant impact on hospital stay or NEC incidence. This secondary analysis supports optimizing preterm formulas and warrants further investigation into long-term immune benefits.